Answer:
<h2>0.</h2>
Step-by-step explanation:
First, we should line up the fractions.
6 / 7 - 6 / 7.
Second, we subtract straight across since denomionators are the same.
6 / 7 - 6 / 7 = 0.
Therefore, the difference is 0.
Answer:
<em>(D). (3, 1) </em>
Step-by-step explanation:
y ≤ 3x - 4
<u><em>(A). (0, 4)</em></u>
4 ≤ 3(0) - 4
4 ≤ - 4 <u><em>(False statement)</em></u>
<u><em>(B). (-2, 0)</em></u>
0 ≤ 3(- 2) - 4
0 ≤ - 10 <u><em>(False statement) </em></u>
<u><em>(C). (0, 0)</em></u>
0 ≤ 3(0) - 4
0 ≤ - 4 <u><em>(False statement)</em></u>
<u><em>(D). (3, 1)</em></u>
1 ≤ 3(3) - 4
1 ≤ 5 <u><em>(True statement) </em></u>
Answer:
2 students in each group
Step-by-step explanation:
If there were 5 groups and after a while 7 students leave early and 3 students remain to do the activity, if you add 7 + 3 = 10 divide it by 5, the number of groups in the activity, you would get 2 students in each group.
1/2
When you put a square root into exponential form, the square root turns into an exponential fraction. Since the square root is 2, our fraction would be 1/2
If our root was a cube root, our exponent would be 1/3, etc.
Answer:
1. 10m
2. 18 ft
Step-by-step explanation:
These are just ratios. They are both essentially doubling